Aplikasi Tracer Study Alumni Universitas Katolik Santo Thomas - Pakpahan, Sorang (LPPM UNIKA Santo Thomas Medan, 2019)
ABSTRACT Catholic University of Saint Thomas is one of the private universities in North Sumatra that was founded in 1984. Currently Unika Saint Thomas has 8 faculties with 16 study programs that have produced many undergraduate graduates. Graduates' data have not been properly stored in each unit so that they will find it difficult to record the alumni. To evaluate a tertiary institution, a number of information systems are needed to support the data storage of the alumni, data on graduation years, place of work, work suitability and waiting time to get a job. To meet the obstacles in obtaining data from alumni, an information system for tracer study is needed. The tracer study application is used as a medium in obtaining information from graduates on the learning process during college studies needed in the world of work. This application is built based online with the Hypertext Preprocessor (PHP) programming language, MySQL database server which makes it easy for alumni to fill out questionnaires and profiles from the websites provided.